Digital gene expression analyses of mammary glands from meat ewes naturally infected with clinical mastitis - Taotao Li; Jianfeng Gao; Xingxu Zhao; Youji Ma (Royal Society Open Science, 2019)
Clinical mastitis in sheep has gravely restrained production performance for a long time. Knowledge of mechanisms of its pathogenesis and resistance in meat sheep mammary gland with clinical mastitis are not yet understood, especially for clinical mastitis caused by natural infection. In this work, RNA-sequencing was firstly used to screen the differentially expressed genes (DEGs) in clinical mastitic mammary tissues (CMMTs) when compared with healthy mammary tissues (HMTs) from meat sheep flocks. We identified 420 DEGs including 316 upregulated and 104 downregulated genes in CMMTs. Gene ontology annotation revealed these DEGs were mainly engaged in immune response and inflammation response. Pathway enrichment showed they were primarily enriched in pathways relevant to inflammation, immune response and metabolism. Alternative splicing analysis showed most common differential splicing genes in CMMTs and HMTs were implicated in immune response. Immunostaining for three immune response-related proteins encoded by DEGs were mainly observed in mammary epithelium from both CMMTs and HMTs, and their positive signals were more intensive in CMMTs than those in HMTs. These findings provide experimental basis and reference for further researching the molecular genetic mechanisms, particularly immune defence mechanisms, of sheep mammary gland during clinical mastitis.